AN EXPLORATION MODEL MEDIATING OF ENGAGEMENT TO EVALUATE PERSONNEL PERFORMANCE AT TRAFFIC POLICE UNIT - Muhammad Sugindo; Retno Kusumastuti Hardjono (Halu Oleo University, 2025)
At the traffic police unit, balancing personnel performance with the developing era became a serious challenge for the police institution to enhance a positive image in society, which requires commensurate efforts to improve the main elements related to performance. Therefore, this study aimed to assess and analyse the effect of personnel satisfaction, training, and management standard on personnel performance through the exploration mediating effect of personnel engagement. Recorded, 123 personnel gave their responses to the questionnaires proposed. Then, it was analysed by the structural equation model technique with the assistance of SmartPLS version software. results stated that the effect of training is not significant in improving personnel performance through engagement, but personnel performance is significantly affected by satisfaction and management standards through engagement.